23 years water level monitoring through earthfill dam (case study) - Moayedi, Hossien; Huat, Bujang B.K.; Moayedi, Fatemeh; Mohammad, Thamer Ahmad Ahmad Mohammad; Parvizi Fard, Ali Akbar; Moghaddam, Arash Ansari (My University, 2011)
Batu Dam is a multi-purpose flood control and a water supply dam. Its construction began in mid 1984 and was completed in mid 1987. By operating the Batu dam and increasing the water level in reservoir, flooding in downstream areas have been reduced. It should be mentioned that the reservoir can now provide an additional of 25 million cubic meters of municipal and industrial water supply to the Klang Valley. Batu dam is a zoned embankment dam with an ungated side channel spillway on the left abutment and an outlet Chute structure, also on the left side of the valley. Present study has aimed to review last 23 years seepage through the body of Batu dam. As a result water level always tend to be at a constant level of EL=+102.7m. Although, there was no need using chute system as for operating spillway according to such water level selection. © 2011 ejge.
Keywords: Batu dam; Earth fill dam; Finite element analysis; Geo seep; Seepage